Nasopharyngeal mantle cell lymphoma with IGH/CCND1 rearrangement and MALT1 amplification: A case study with literature review - Ming Xie; Hongwei Ma (Elsevier, 2020)
Mantle cell lymphoma (MCL) is an aggressive B cell lymphoma and characterized by the t(11;14)(q13;q32)/CCND1+. MALT1 amplification is the most common genetic event in MALT lymphomas. Identification of CCND1 and MALT1 gene over expression plays a key role in the diagnosis of MCL and some MALT lymphomas. Several unusual variants of MCL have been described with variable morphological, immunophenotypic and genetic characteristics. Here, we report an unusual nasopharyngeal B cell lymphoma with both CCND1 rearrangement and MALT1 amplification. The patient was a 60 year old gentleman admitted for further evaluation of "unspecified lymphoma". PET oncology study revealed intense FDG avidity in the nasopharyngeal region, highly suspicious for malignancy. A biopsy of nasopharyngeal lesion was performed. Histological examination showed focal expansion of mantle zone surrounding residual germinal centers. Flow cytometry demonstrated one population of monoclonal B cells, negative for CD23 with variable CD5 expression. Lymphocytes in mantle zone were positive for CD20, BCL1 and weakly CD5 by immunohistochemistry. Interestingly, FISH studies were positive for standard and variant IGH/CCND1 rearrangement (85%) and MALT1 gene amplification (60%). Staging evaluations showed minimal bone marrow lymphoma involvement and increased FDG avidity in bilateral tonsillar regions and regional nodes of the neck, indicative of systemic disease. The overall findings were consistent with primary nasopharyngeal mantle cell lymphoma, which harbored both CCND1 and MALT1, with systemic involvement. The patient responded well with chemotherapy. To our knowledge, this is the first such case reported in the literature. Recent studies have shown that MALT1 gene may involve in the MYC pathway regulation in MCL, which represents a promising target for future therapies in MCL patients.